Securing data transmission by cryptography using Rohit integral transform - Rohit Gupta; Rahul Gupta (International Journal of Engineering and Technology, 2023)
The encryption and decryption processes to secure data transmission and protection in cryptography are very useful in a communication system for authentication and privacy. Recently, integral transform techniques have been used by many researchers to increase the strength of encryption and decryption processes in cryptography. In this paper, the ability of Rohit integral transform (RIT) is shown for the encryption and decryption processes in cryptography and in general, in the field of data security through practical application.